Language nests and cultural immersion environment as new methods for english teaching learning process at “grandes genios” nursery bilingual center during the academic cycle march-august 2014 - Cando Gutiérrez, Gina Lorena (2015)
This present project was focused on improving the English teaching-learning process in Initial I and Initial II levels at “Grandes Genios Nursery Bilingual Center”, which is located in Latacunga city. At this institution English is taught to children from 3 to 5 years old. In a way that, children have the opportunity to acquire a foreign language through immersion methodology. However, nursery bilingual centers have been applying common methods and they do not teach English through cultural activities, as result, it does not allow social interaction. That is why, this investigation was focused on including two English syllabuses for Initial I and Initial II based on innovative methods: “Language Nest and Cultural Immersion Environment” in the institutional curriculum; which contribute to guide to teacher about curricular elements, especially; how to apply the mentioned methods....